Genetic analysis for bacterial blight resistance in indica rice (Oryza sativa L.) cultivars - Kumar, Manish; Singh, Ravi Pratap; Singh, Onkar Nath; Singh, Prakash; Arsode, Pandurang; ., Namrata; Chaudhary, Madhu; Jena, Debarchana; Singh, Vineeta; Rout, Diptibala; Mukherjee, Arup Kumar; Samantaray, Sanghamitra; et al. (ORYZA-An International Journal of Rice, 2019)
Prior information on genetics of bacterial blight (BB) resistance (R) genes is imperative for its successful utilization in trait development and breeding for new resistant varietiesin rice. This experiment was aimed to assess the genetics of BB resistance in susceptible but popular rice variety HUR-917 and IRBB 66 (isogenic lines of IR 24) which harbors five R genes. Bioassay results in the parental lines and crosses were revealed resistance and susceptible disease response in R gene(s) positive and negative lines, respectively with varying range of Xoo (Xanthomonas oryzae pv oryzae) pathotype specificity. Phenomics of F2 and Back Cross (BC) generations showed existence of non-allelic interaction (13:3) between R genes with substantial variability in disease severity. The plants carrying mono hetero-allelic R gene has exsertedModerately susceptible (MS) disease reaction with 6.42 to 8.86 disease severities, however, lines carrying 2 R gene(s) could be able to disease severity Moderate susceptible MS to Moderate Resistant MR against all pathotypes existing in the region make it valid that the doses complementarity and presence of interaction in R genes are major determinant in R expression. It was recorded that presence of two or more R genes (Xa21+xa13; Xa21+ xa13+xa5) exerted broad spectrum BB resistance, hence found more suitable to combat this disease in HUR-917.